Avaliação da alteração da modalidade tarifária de uma estação de tratamento de água - Castro, Antonio Natan dos Santos (Universidade Federal do Tocantins, 2019)
The electrical energy is the main input for the process of treatment of water and effluents, represented one of the most significant operational costs in sanitation companies. According to data from the National System of Information on Sanitation (SNIS) in 2016, the sanitation service providers consumed more than 11.8 TWh, with a pantry of R$ 5.41 billion, distributed between water treatment and sanitation. The efficient use of electrical energy, in addition to allow greater financial return by the reduction of production costs, make better use of existing electromechanical and civil infrastructure and the postponement of the application of resources for expansion of the systems. In this context, the objective of this study is to assess, as the operational characteristics of electric energy consumption, the most efficient way to bill a Water Treatment Station along the concessionaire of energy. The WTS used for the study is located in the city of Palmas-TO and is responsible for the supply of approximately 75% of the city. Today the station is stocked by a rural network of 34.5 kV, framed in group A3a, retry the structure THS Green and filled by four generators affairs at the time. Because of the successive problems with continuity of supply of rural line appeared beside the technical body for the possibility of amendment of supply from the station to the character of subtransmissão, for a 138 kV line that passes along the plant. For this reason, will be examined in the economy was made with the change in the price of the applied tariff, along the specificity of the calculation of the invoice from the station. For the analysis of economic feasibility will be applying the rules of payback and Net Present Value (NPV), whereas the initial investment of amendment of border processing, labor-intensive technique and trend in changes in rates of the concessionaire for the coming years. With the change, the treatment station should be in toll structure THS Blue, which presents different values for generation and distribution of the current fare, being more flexible for consumption in the peak hours. The purpose of this analysis is not only in the field of the economy with the invoice efficiency of the station, but also to increase the availability of energy that directly impact on the pace of production and service warranty.